Dr. A Strategy for a Thai Hospital - Talib, Ameen (Archives of Business Research, 2020)
The paper proposes a strategy for a Hospital in Thailand. These strategies are chosen based on the goal to be achieved, our current situation and understanding the environment we working in. Prior to adopting any strategies we need to (a) identify the strategic goals (b) identify where we are including our strength and weakness , (c) understand the environment we working in including competitors and economic environment, and (d) suggest a strategy that will achieve the goal and take us from where we are to where we want to go. The strategy needs to work within the environment we are in and take into consideration our current status. The paper is useful for those involved in business strategy.